Impact of Video Podcasts on Speaking Proficiency in Indonesian Higher Education: A Study of Diverse Learning Styles - Wahyuni, Sri; Dewi, Desi Surlitasari (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the effectiveness of video podcasts as a supplementary tool for enhancing speaking proficiency among second-semester higher education students majoring in English, with varying learning styles. It examines the impact of video podcasts on speaking proficiency across visually-dominant, auditory-dominant, and kinesthetic-dominant learners and explores the differences in effects among these three learning styles. It involved 42 respondents, specifically within an Intermediate Speaking course, categorized into three groups based on their dominant learning styles: visual, auditory, and kinesthetic. Data were analysed through paired sample t-tests and one-way ANOVA. The result shows that visually-dominant learners improved from a pretest mean of 60.24 to a posttest mean of 67.48 (p = .000), auditory-dominant learners increased from 60.36 to 66.73 (p = .001), and kinesthetic-dominant learners showed an increase from 64.33 to 72.83 (p = .022). Despite these improvements, the one-way ANOVA indicated no statistically significant differences in the level of improvement among the three learning styles (p = .707) which implies that video podcasts are effective across different learning styles. This study’s findings contribute to the understanding of multimedia tools' role in language learning and the positive impact of utilizing video podcasts on speaking proficiency. The flexibility of video podcasts enables students to learn at their own pace, revisit content, and receive personalized feedback, which can be particularly beneficial for students with different learning styles.